Implementasi Media Tong Ja Li untuk Meningkatkan Hasil Belajar Perkalian Siswa Kelas III - Astrid Azzahra; Sari, Elok Fariha (Jurnal Gentala Pendidikan Dasar, 2025)
This study explores the effectiveness of the Tong Ja Li (Kantong Jago Kali) approach in improving mathematics learning outcomes among third-grade students, a concrete and interactive learning media designed to enhance understanding of multiplication. The background of this research lies in the challenges students face in mastering multiplication due to conventional and less engaging teaching methods. This research employed a quasi-experimental method with a nonequivalent control group design, conducted at SDN Sampangan 02 Semarang during the 2025/2026 academic year. The study involved two classes: the experimental group used Tong Ja Li, while the control group received traditional instruction. Data collection included tests, observations, interviews, and documentation. The study found that students in the experimental group scored significantly higher on the post-test than students in the control group. These findings indicate that Tong Ja Li is effective in helping students understand multiplication concepts through concrete, visual activities. It is concluded that Tong Ja Li can be an alternative solution to support elementary mathematics learning and increase students’ motivation and achievement.